Determination of Multi-performance Characteristics in Electric Discharge Machining of DIN 1.2767 Steel Using Grey Relational Analysis - Fatatit, Abubaker Y.; Kalyon, Ali (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Electric discharge machining (EDM) is one of the most important unconventional machining processes, which can cut hard materials and complex shapes that are difficult to machine by conventional machining processes easily and with high accuracy. In this study, L18 orthogonal array combined with gray relational analysis (GRA) is implemented to investigate the multiple performances characteristics in EDM of DIN 1.2767 Tool Steel. Machining process parameters selected were discharge current (Ip), pulse-on time (Ton), pulse-off time (Toff), and electrode material (copper alloys [NSS and B2]). The investigated performances characteristics were tool wear rate (TWR) and material removal rate (MRR). Analysis of variance (ANOVA) and Taguchi’s signal-to-noise ratio with the help of Minitab-17 software were used to analysis the effect of the process parameters on TWR and MRR. The experimental results and data analysis reveal that TWR and MRR are more affected by Ip and Ton. The minimum TWR was obtained at parametric combination Ip (6A), Ton (800 μs), and Toff (800 μs) and the maximum MRR attained at Ip (25A), Ton (800 μs), Toff (200 μs), and NSS electrode. After applying GRA, the optimal parametric combination for MRR and TWR was determined as Ip (25A), Ton (800 μs), Toff (200 μs), and NSS electrode. The study also exhibited the occurrence of an interaction between the variables on the responses. In addition, scanning electron microscopy images showed that the metal surface was affected with the increase in Ton and Toff.